The Influence Of Organizational Commitment On Employee Job Satisfaction Through Servant Leadership On The It&B Campus - Agus Susanto (Cita konsultindo, 2024)
The objective of this study is to investigate the correlation between organizational commitment, servant leadership, and employee job satisfaction in the IT&B campus setting. Organizational commitment is often seen as a vital factor that influences employee performance and loyalty. Similarly, servant leadership is seen as a leadership style that promotes employee service and strengthens the bond between leaders and followers. This study use a quantitative methodology to provide a detailed and explanatory analysis. To gather data from individuals employed in different departments of the IT&B campus, we will employ a survey methodology and administer a questionnaire. The population for this study comprises all 51 people currently employed at the IT&B Campus. The sampling strategy utilizes a saturated sample approach, where the whole population is used as the study sample. We do data analysis using Smart PLS through several sources. The research seeks to get a comprehensive knowledge of the elements that impact employee work satisfaction in educational institutions such as IT&B campuses. It also intends to give practical advice to campus management on how to improve employee well-being and performance. We anticipate that the research's findings will establish a basis for developing more efficient management policies and practices within the IT&B campus environment and comparable institutions.